Dishwashing Soap from Waste Cooking Oil - Mohd Zulwazi, Nur Maisarah; Azmi, Nurin Arina; Nawi, Adnin Afifi (Multidisciplinary Applied Research and Innovation, 2023)
Waste cooking oil is usually dumped, resulting in waste and environmental damage if not disposed properly. Many stores sell dishwashing detergent that contain hazardous chemical in it and it might irritate people’s skin and health when they use it. Organic components, such as waste cooking oils, were used in this project. This dishwashing soap was developed with the goal of producing low cost and environmentally friendly soaps. The pH and total fatty matter tests were performed on the four formulations, namely Formulation 1 Formulation 2 Formulation 3 and Formulation 4 The results show that the pH was 7.52 8.74 9.67 10.34 and 11.20 for Formulation 1 Formulation 2 Formulation 3 Formulation 4 and dishwashing soap from store respectively. For total fatty matter test, the value is 74.49% 75.68% 75.87% 76.95% and 76.70% for Formulation 1 Formulation 2 Formulation 3 Formulation 4 and dishwashing soap from store respectively. As a result, it was found that Formulation 3 is the best among the other three formulations because the pH and the total fatty matter for this formulation are 9.67 and 75.87% which is safe to use on skin and has a moisturizing effect.